Explore BrainMass

Explore BrainMass

    The Logic of a Mathematical Equation

    Not what you're looking for? Search our solutions OR ask your own Custom question.

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    Please response to the following: Reason each step and explain the mathematical mistake if there is one.

    (a+b)(a-b) = b(a-b)

    © BrainMass Inc. brainmass.com December 24, 2021, 4:46 pm ad1c9bdddf

    Solution Preview

    (a+b)(a-b)=b(a-b)==>a+b=b by dividing both sides by a-b
    So a+b=b==>a=0.
    Obviously, if ...

    Solution Summary

    This solution is comprised of 55 words and examines the statement (a+b)(a-b) = b(a-b). All work is shown.